Ensuring Optimal Community HIV Testing Services in Nigeria Using an Enhanced Community Case-Finding Package (ECCP), October 2019–March 2020: Acceleration to HIV Epidemic Control - Jahun I; Dirlikov E; Odafe S; Yakubu A; Boyd AT; Bachanas P; Nzelu C; Aliyu G; Ellerbrock T; Swaminathan M (HIV/AIDS: Research and Palliative Care, 2021)
Ibrahim Jahun,1 Emilio Dirlikov,2 Solomon Odafe,1 Aminu Yakubu,1 Andrew T Boyd,2 Pamela Bachanas,2 Charles Nzelu,3 Gambo Aliyu,4 Tedd Ellerbrock,2 Mahesh Swaminathan1 On behalf of CDC Nigeria ART Surge Team1US Centers for Disease Control and Prevention, Division of Global HIV and TB, Center for Global Health - Nigeria, Abuja Federal Capital Territory, Nigeria; 2US Centers for Disease Control and Prevention, Division of Global HIV and TB, Center for Global Health, Atlanta, GA, USA; 3Federal Ministry of Health (FMOH), Abuja, Nigeria; 4National Agency for the Control of AIDS (NACA), Abuja, Federal Capital Territory, NigeriaCorrespondence: Ibrahim JahunCenters for Disease Control and Prevention (CDC)-Nigeria, Embassy of the United States of America, Central Business District, Abuja, Federal Capital Territory, NigeriaTel +234 8037013715Email drjahun@yahoo.co.ukPurpose: The 2018 Nigeria HIV/AIDS Indicator and Impact Survey (NAIIS) showed Nigeria’s progress toward the UNAIDS 90-90-90 targets: 47% of HIV-positive individuals knew their status; of these, 96% were receiving antiretroviral therapy (ART); and of these, 81% were virally suppressed. To improve identification of HIV-positive individuals, Nigeria developed an Enhanced Community Case-Finding Package (ECCP). We describe ECCP implementation in nine states and assess its effect.Methods: ECCP included four core strategies (small area estimation [SAE] of people living with HIV [PLHIV], map of HIV-positive patients by residence, HIV risk-screening tool [HRST], and index testing [IT]) and four supportive strategies (alternative healthcare outlets, performance-based incentives for field testers, Project Extension for Community Healthcare Outcomes, and interactive dashboards). ECCP was deployed in nine of 10 states prioritized for ART scale-up. Weekly program data (October 2019–March 2020) were tracked and analyzed.Results: Of the total 774 LGAs in Nigeria, using SAE, 103 (13.3%) high-burden LGAs were identified, in which 2605 (28.0%) out of 9,294 hotspots were prioritized by mapping newly identified PLHIV by residential addresses. Over 22 weeks, among 882,449 individuals screened using HRST, 723,993 (82.0%) were eligible and tested for HIV (state range, 43.7– 90.4%), out of which 20,616 were positive. Through IT, an additional 3,724 PLHIV were identified. In total, 24,340 PLHIV were identified and 97.4% were linked to life-saving antiretroviral therapy. The number of newly identified PLHIV increased 17-fold over 22 weeks (week 1: 89; week 22: 1,632). Overall mean HIV positivity rate by state was 3.3% (range, 1.8– 6.4%).Conclusion: Using ECCP in nine states in Nigeria increased the number of PLHIV in the community who knew their status, allowing them to access life-saving care and decreasing the risk of HIV transmission.Keywords: ART Surge, small area estimation, HIV risk assessment tool, index partner testing